Verification of radio frequency pasteurization process for in-shell almonds. (January 2017) - Li, Rui; Kou, Xiaoxi; Cheng, Teng; Zheng, Ajuan; Wang, Shaojin
Abstract: Salmonella outbreaks related to consumption of raw almonds have forced nut industry to seek effective pasteurization processes. Radio frequency (RF) treatment is a potential pasteurization method for controlling Salmonella while maintaining product quality. Escherichia coli ATCC 25922 is nonpathogenic and can be used as a surrogate of pathogenic Salmonella when their thermo-tolerances are equivalent. Since thermal resistance of target pathogens can be reduced by raising water activity in dry samples, the aim of this study was to explore the application of RF treatments to control E. coli ATCC 25922 in pre-washed in-shell almonds without quality losses. A 6 kW, 27.12 MHz RF heating system was used to rapidly pasteurize 1.7 kg washed in-shell almonds together with hot air heating at 55 °C. To meet effective pasteurization requirements and maintain almond quality, the RF treatment protocol was obtained by using an electrode gap of 10.5 cm for pasteurization, 12 cm for drying, and followed by forced room air cooling in 3 cm thick samples. The results showed that the RF heating at the electrode gap of 10.5 cm for 1.5 min achieved 5-log reductions of E. coli ATCC 25922 and the followed RF drying for 8.5 min reduced the moisture content of almond shell back to 5.08% w.b. Kernel color, peroxide value, weight loss, fatty acid value and fatty acid composition of RF treated almonds met good quality standard used by almond industry. Therefore, RF treatments are an effective and rapid heating method to control Salmonella in pre-washed in-shell almonds. Highlights: Escherichia coli ATCC 25922 could be used as a surrogate of pathogenic Salmonella. Washed in-shell almonds inoculated with E. coli were treated by RF energy. RF treatment protocol included washing, pasteurization, drying and cooling. Almond quality was still acceptable by nut industry after RF treatment and storage.